Hepatitis B vaccine co-administration influences the heterologous effects of neonatal BCG vaccination in a sex-differential manner. Issue 9 (23rd February 2022) - Pittet, Laure F.; Cox, Lianne; Freyne, Bridget; Germano, Susie; Bonnici, Rhian; Gardiner, Kaya; Donath, Susan; Collins, Clare L.; Casalaz, Dan; Robins-Browne, Roy; Flanagan, Katie L.; Messina, Nicole L.; et al.
Highlights: BCG vaccination reduced IFN-γ and MCP-1 responses to heterologous stimulants. HBV vaccination alone did not alter heterologous cytokine responses. Males overall produced more IFN-γ and TNF-α compared with females. HBV co-administration influenced the heterologous effects of neonatal BCG vaccination in a sex-differential manner. Abstract: Introduction: Bacille Calmette-Guérin (BCG) and hepatitis B (HBV) vaccines are frequently given concomitantly at birth. Neonatal BCG vaccination induces off-target immunological effects. Whether HBV vaccine has immunomodulatory effects is unknown. As off-target effects might vary when vaccines are given simultaneously, this randomised controlled trial aimed to evaluate the influence of neonatal vaccination with BCG and/or HBV on heterologous immune responses. Methods: A total of 185 neonates in Australia were randomised to receive either neonatal BCG-Denmark vaccine, HBV vaccine, both (BCG + HBV group), or none (No vaccine group). In-vitro responses to heterologous stimulants were assessed 7 days after vaccination. The influence of (i) randomisation group and (ii) sex on interferon-gamma (IFN-γ), monocyte chemoattractant protein-1 (MCP-1), and tumour necrosis factor-alpha (TNF-α) responses was analysed using linear regression. Results: Overall, BCG vaccination alone or with HBV co-administration reduced IFN-γ and MCP-1 responses to heterologous stimulants. HBV vaccination alone did not alter heterologous cytokine responses. In general, males produced more IFN-γ and TNF-α than females. We observed a sex-differential effect in relation to the influence of HBV co-administration on the effect of BCG on heterologous responses. Compared with males in the No vaccine group, males in the BCG + HBV group had lower IFN-γ and MCP-1 responses. In contrast, compared with females in the No vaccine group, females in the BCG group had higher IFN-γ response and lower MCP-1 responses. Conclusion: Neonatal BCG vaccination resulted in lower cytokine responses to unrelated pathogens. HBV co-administration did not have a significant impact on responses overall but influenced the heterologous effects of neonatal BCG vaccination in a sex-differential manner.